The nucleotide sequence of human tRNAGly (anticodon GCC). - Gupta, R C (1979)
The sequence of tRNAGCCGly from human placenta was determined by recently developed postlabeling techniques. The tRNA was digested completely with RNases T1 and A in the presence of alkaline phosphatase, the oligonucleotides were 3'-terminally (3H)-labeled, mapped on PEI-cellulose thin layers, isolated, and sequenced by methods based on base-specific cleavages. Overlaps were obtained by readout sequencing techniques on polyacrylamide gels and PEI-cellulose thin layers. The thin-layer readout technique was used also to locate and identify modified nucleotides. The primary structure was found to exhibit a large degree of homology (94.6%) with silkworm tRNAGCCGly but only 67.6% homology with human tRNACCCGly.